2011
DOI: 10.1128/jb.01500-10
|View full text |Cite
|
Sign up to set email alerts
|

The Genome of Erysipelothrix rhusiopathiae, the Causative Agent of Swine Erysipelas, Reveals New Insights into the Evolution of Firmicutes and the Organism's Intracellular Adaptations

Abstract: Erysipelothrix rhusiopathiae is a Gram-positive bacterium that represents a new class, Erysipelotrichia, in the phylum Firmicutes. The organism is a facultative intracellular pathogen that causes swine erysipelas, as well as a variety of diseases in many animals. Here, we report the first complete genome sequence analysis of a member of the class Erysipelotrichia. The E. rhusiopathiae genome (1,787,941 bp) is one of the smallest genomes in the phylum Firmicutes. Phylogenetic analyses based on the 16S rRNA gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
113
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 79 publications
(123 citation statements)
references
References 58 publications
3
113
0
Order By: Relevance
“…Recently, we sequenced the genome of E. rhusiopathiae and reported that E. rhusiopathiae is phylogenetically related to Mollicutes (Mycoplasma species) (17). Based on genomic phylogenetic trees, we proposed that E. rhusiopathiae and other Erysipelotrichia strains may be separate from Firmicutes and classified as a distinct phylum (17).…”
mentioning
confidence: 99%
“…Recently, we sequenced the genome of E. rhusiopathiae and reported that E. rhusiopathiae is phylogenetically related to Mollicutes (Mycoplasma species) (17). Based on genomic phylogenetic trees, we proposed that E. rhusiopathiae and other Erysipelotrichia strains may be separate from Firmicutes and classified as a distinct phylum (17).…”
mentioning
confidence: 99%
“…ACLK 00000000.2), was obtained from the National Center for Biotechnology Information (NCBI) database (http://www.ncbi.nlm.nih.gov/genomes /MICROBES/microbial_taxtree.html) and compared to the sequence of Fujisawa (accession no. AP012027) (2). ATCC 19414 strain-specific coding sequences (CDS) with a putative choline-binding domain (the GW module) at the C terminus were identified.…”
Section: Methodsmentioning
confidence: 99%
“…E. rhusiopathiae has been referred to as the "walled relative" of mycoplasma (1), and E. rhusiopathiae is phylogenetically close to Mollicutes (a class that includes the genus Mycoplasma); the genomic features of this organism represent evolutionary traits of both Firmicutes and Mollicutes (2,3).…”
mentioning
confidence: 99%
See 2 more Smart Citations